Storage Characteristics of Ready to Serve Fried Thelly Prawns (Metapenaeus dobsoni) at Ambient Temperature - A.C., Joseph; P.V., Prabhu; V., Narayanan Nambiar (Fishery Technology, 2025)
Results of a study on the storage characteristics of ready to serve dried and fried prawns (Metapenaeus dobsoni) packed in polyester/polythene bags and stored at ambient temperature (22-28Â°0 are presented. Treatments with common salt (sodium chloride) and citric acid prior to initial SWl drying is found to enhance both quality and shelf-life of the final fried product. While the untreatcd dried and fried prawns showed a storage life of 42 days, the test sample remained in acceptable condition upto 55 days. Dried and fried prawns appear to be a promising and appealing ready to serve product, ideally suited for the urban consumer market.